Against Physical Violence Of Mrs.Popova In Anton Checkov's The Brute Drama (1977) : A Feminist Approach - Dewi, Astari Kirana (2012)
The major issue of this study is; how is the physical violence of Mrs. Popova in Anton Checkov The Brute drama related with feminism approach. The objective of this study is to analyze the novel in terms of its structural elements and to analyze the novel based on the feminist perspective. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. The primary data will be taken from Checkov's drama Script The Brute, while the secondary data are taken from the other data, which have relation with the research, the underlying theory (feminism perspective), Russian feminism and other materials concern to the analysis. The data collection method is reading the drama script more than just one, until the researcher gets the message offered from the script and gets an adequate information or data to be analyzed, reading some other resources related to the theories, taking notes for the important parts both in primary and secondary sources in data cards. The note can be book or computer. Classifying the data into categories and develop them into a good unit and making conclusion. The results of the study show; Rebels against Patriarchal System in The Brute drama shows that Mrs. Popova as a woman feels that she cannot live without her husband. Mrs. Popova is begging to Smirnov because she cannot do anything with the condition of her on that time related with the money. Women's Position in The Brute drama shows that the position of women is absolutely subordinated to men, especially Mrs. Popova. Mrs. Popova is a woman and as a wife. As a wife, she knows her position that she has to keep loyal to her husband, even her husband is dead. There are only two women's rights that appeared in Mrs. Popova personality. The first is the right to get respect and the second is the right for love and being loved. The role of women in The Brute drama appears when Mrs. Popova tries to protect her grade and status as wife and as widow. She does this to protect her status because Smirnov has condescended her.